The Terms Used For Woman's Veil In The Pre-Islamic (Jahili) Poetry: A Pragmatic Study - Shereefah Ibrahim Muhamad Bin Taleb (Ijaz Arabi Journal of Arabic Learning, 2023)
The present research intends to investigate the names used for the woman's veil in pre-Islamic poetry (Jahili Poetry) using a pragmatic method to determine the significance of those phrases, how they were passed down through the generations, and how they evolved. The study will be conducted along three axes: the pragmatic approach concept, the status of the veil among Arabs, and the presentation of specific terms and texts relevant to the veil, as well as a "lexical semantic analysis" of those terms. Research findings and suggestions: The poetry of Jahili contains a plethora of tongues for woman's vile. Poets utilized them in various ways based on the conditions of women and their social standing since women can be free, enslaved, urban, nomadic, large, and little. Research on the languages and components of the woman's veil throughout Islamic history should be prioritized. Additionally, the interrelationships between the modern and ancient veil should be investigated, and its importance and cultural and literary qualities should be sought through literary texts of poetry and prose. Overall, the study of pre-Islamic poetry and the veil can significantly impact the teaching of Arabic. By gaining a deeper understanding of the Arabic language's cultural, social, and linguistic aspects, students can better appreciate the historical context and cultural richness of the language. This research can provide important insights into the interrelationships between the modern and ancient veil and can help to deepen students' understanding of the language and its use throughout history.